2020
DOI: 10.1111/jpc.14824
|View full text |Cite
|
Sign up to set email alerts
|

Teacher rating versus measured academic achievement: Implications for paediatric research

Abstract: AimTo determine whether teachers' reports of student academic performance can suffice for research purposes by comparing it with a curriculum‐based standardised test.MethodsIn this longitudinal cohort study of children born at risk of neonatal hypoglycaemia, teachers' global assessment of student performance was compared with assessment tools for teaching and learning (asTTle) at 9–10 years. Performance on asTTLe was rated as being below, at or above that expected on the national curriculum for year and term o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The e-asTTle assesses students’ performance in Curriculum Levels 2 to 6 (nominally, school years [grades] 4 to 11; approximately ages 8 to 16 years), with normative data for each year and term of schooling (4 terms per year) for years 4 to 12 inclusive . The psychometric properties and scoring methods have been detailed elsewhere . In brief, a student’s achievement was rated as being “at” curriculum level if their achievement was within the range of the normative data for students in the 3 terms either side of their current school year and term, “above” if 4 or more terms above, “below” if 4 to 7 terms below, or “well below” if 8 or more terms below their school year and term.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The e-asTTle assesses students’ performance in Curriculum Levels 2 to 6 (nominally, school years [grades] 4 to 11; approximately ages 8 to 16 years), with normative data for each year and term of schooling (4 terms per year) for years 4 to 12 inclusive . The psychometric properties and scoring methods have been detailed elsewhere . In brief, a student’s achievement was rated as being “at” curriculum level if their achievement was within the range of the normative data for students in the 3 terms either side of their current school year and term, “above” if 4 or more terms above, “below” if 4 to 7 terms below, or “well below” if 8 or more terms below their school year and term.…”
Section: Methodsmentioning
confidence: 99%
“…18 The psychometric properties and scoring methods have been detailed elsewhere. 19 In brief, a student's achievement was rated as being "at" curriculum level if their achievement was within the range of the normative data for students in the 3 terms either side of their current school year and term, "above" if 4 or more terms above, "below" if 4 to 7 terms below, or "well below" if 8 or more terms below their school year and term. Additionally, children's teachers were asked to rate their academic achievement against the expected curriculum level for school year and term (well below, below, at, or above) and in relation to peers (much worse, worse, about the same, better, or much better) using a structured teacher questionnaire.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, academic achievement was assessed using the Assessment Tools for Teaching and Learning (e-asTTle), a standardized curriculum-based online achievement test for Reading Comprehension/Pānui and Mathematics/Pāngarau [9, 10]. The child’s performance was rated as at, above, below, or well below the normative range at that curriculum level.…”
Section: Methodsmentioning
confidence: 99%
“…If the judges had been free from bias, the degree of mismatch between judgement and score should have been small and constant across all groups. A number of explanations for this discrepancy exist, including variable teacher expectations by student demographic factors, students' variable familiarity and practice with standardised tests, mismatch of teaching to test content, lack of OTJ moderation among teachers, or even unconscious bias (Shah et al, 2020). 'Otunuku and Brown (2007) even suggested that teachers may be delivering a curriculum that disguises from Māori and Pasifika students that their performance is well below expectations.…”
mentioning
confidence: 99%